2021
DOI: 10.1186/s43556-021-00044-1
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Kinase 1 (Chk1) inhibition fails to activate the Stimulator of Interferon Genes (STING) innate immune signalling in a human coculture cancer system

Abstract: Utilising Checkpoint Kinase 1 (Chk1) inhibitors to increase cytoplasmic DNA may be a potential strategy to increase the sensitivity of tumours to immune checkpoint modulators. The appearance of DNA in the cytoplasm can drive Cyclic GMP-AMP Synthase-2′,3′-Cyclic Guanosine Monophosphate–Adenosine Monophosphate-Stimulator of Interferon Genes (cGAS-cGAMP-STING) inflammatory, anti-tumour T-cell activity via a type I interferon (IFN) and nuclear factor-κB response. In the THP1-Dual reporter cell line, the STING agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…However, dysregulation of cGAS-STING observed here in both human and mouse melanomas appears to be a common feature of melanomas that contributes to the immune evasion of these tumours [44]. Furthermore, it has recently been reported that CHK1i does not activate cGAS-STING signalling even in cells where this pathway is functional, and actually inhibits cGAS-STING pathway activation of IRF3 [45]. The ability of CHK1i+LDHU to promote strong pro-inflammatory cytokine/chemokine expression independent of this pathway suggests other pathways such as NF-κB observed in mouse melanoma.…”
Section: Discussionmentioning
confidence: 59%
“…However, dysregulation of cGAS-STING observed here in both human and mouse melanomas appears to be a common feature of melanomas that contributes to the immune evasion of these tumours [44]. Furthermore, it has recently been reported that CHK1i does not activate cGAS-STING signalling even in cells where this pathway is functional, and actually inhibits cGAS-STING pathway activation of IRF3 [45]. The ability of CHK1i+LDHU to promote strong pro-inflammatory cytokine/chemokine expression independent of this pathway suggests other pathways such as NF-κB observed in mouse melanoma.…”
Section: Discussionmentioning
confidence: 59%
“…The checkpoint kinase 1 (CHK1) inhibitor prexasertib induces DNA damage in cancer cells and activates the STING/TBK1/IRF3 innate immune pathway 106 , thereby increasing levels of chemokines such as CXCL10 and CCL5, and inducing activation of cytotoxic T lymphocytes 107 . Another study has reported that CHK1 inhibition increases TBK1 phosphorylation but not IRF3 phosphorylation, and does not induce IRF or NF-κB reporter gene activation 108 . In a phase II trial on recurrent ovarian cancer, treatment with prexasertib has been found to upregulate activation markers of the STING pathway such as TBK1, which correlates with prolonged progression-free survival (9 months vs. 3 months, P = 0.003) 109 .…”
Section: Strategies For Harnessing the Cgas-sting Pathway In Cancer T...mentioning
confidence: 99%
“…In conjunction with certain cytotoxic therapies, checkpoint kinase 1 (Chk1) inhibition modifies the internal cellular environment but sometimes suppresses expected responses [247]. One proposed solution is to supplement Chk1 inhibitors with STING agonists [248].…”
Section: Immunotherapies Such As Oncolytic Viruses (Ov)mentioning
confidence: 99%